Theoretical simulation of the influence of cathode formulation on lithium-ion battery performance - Miranda, D. (2020)
Optimizing cathode electrode formulation is essential in the development and performance of lithium-ion batteries, as the cathode affects the capacity of the battery. Cathode electrode formulation is based on different materials and relative contents. In this work, the cathode performance for the LiMn2O4, LMO, active material has been obtained by theoretical simulations for different materials formulations and at various discharge rates. Further, the simulations were compared with experimental results. It is demonstrated that the optimization of the electrode formulation strongly depends on the percentage of conductive material, existing a minimum conductive filler content that optimizes the delivered capacity of the battery and being that delivery capacity independent of the conductive filler content for higher concentrations.